The Impact of Household Debt on Domestic Violence (DV) Against Children in Indonesia - Maulitfiani, Anjar; Handayani, Dwini (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
Financial difficulties within a household could contribute to cases of domestic violence (DV). This study investigates the correlation between household debt and occurrences of domestic violence towards children in Indonesia. The study employs a quantitative methodology, notably utilising multinomial logistic regression analysis. Evidence suggests that households with several forms of debt are more prone to exhibiting both psychological and physical domestic violence against children, in contrast to households without domestic violence. This association maintains its significance even after taking into account control variables, such as the age of the spouse, the level of education of the head of home, the spouse's level of education, the size of the household, the perception of domestic violence, the schooling status of the children, and the age of the children are statistically associated with psychological, physical, and both types of domestic violence against children. Policymakers should assess household loan repayment capacity to limit lending to those at risk of financial struggle, while the government should implement parental education programs to raise awareness of child abuse and encourage non-violent parenting techniques.